Filming the Historical Geography: Story from the Realm of Maps in Regensburg - Beata Medyńska-Gulij (MDPI AG, 2021)
Research on a specific topic requires the individualized cartographic methods of work that may be defined as the Realm of Maps. The double dimensionality in the Realm of Maps is understood here as a physical place—a studio workroom—and as a research method. In this study, we focused on the way of presenting a research method designed to study the topic of historico-geographical space in the form of a short film story. The second purpose is to indicate the legitimacy of combining two dimensions of working with maps, the real one and the virtual one, to be able to collect cartographic and descriptive sources in one scientific center. Our research on the Story from the Realm of Maps in Regensburg: ‘People Movement in Southeast Europe’ included a concept adopted by cartographical, historical, and geographical sources; the construction of a studio workroom; a script draft; individual sequences of the story in different types of media; editing the video, along with publishing it on an online video-sharing platform. We used as many different types of geomedia as possible, which, on the one hand, boosts the attractiveness of the film and, on the other, may hamper the proper perception of the main film plot. Finally, we recommend principles of map design for the film, with analog maps and maps created specifically for the short film, published using online video-sharing platforms.